Pengaruh Online Customer Review E-Wom Content Marketing pada Keputusan Pembelian UMKM Semarang melalui Tiktok - Alvarizi, Rizki; Purnamasari, Devi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
Advertising marketing in commercial applications with marketing requirements cannot be separated from the development of visual communication. The Tiktok application plays an important role in advertising marketing media, and commercial applications such as Instagram and Tiktok can be in the database or storage media for business people in carrying out their business processes. The data obtained shows that UMKM players are still lacking in utilizing promotional opportunities through the Tiktok application, so the research conducted aims to provide information related to opportunities for UMKM players and the Tiktok social media user community in increasing product sales. The research was conducted using quantitative methods, where the data obtained is based on numbers and analysis. The results of the research found in the form of data showing the effect of the level of effectiveness of content marketing on significant purchasing decisions.